UPAYA MENINGKATKAN MINAT BELAJARA SEJARAH SISWA KELAS X MELALUI PENERAPAN METODE PEMBELAJARAN SMALL GROUP DISCUSSION DI SMK NEGERI 4 KEPAHIANG - Sintia, Mira; Zafri, Zafri (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research aims to be an initial study of collecting information about students' low interest in learning history by applying the Small Group Discussion learning method to learning History in Vocational High Schools (SMK). This research is a type of Classroom Action Research (CAR) using two cycles, namely Cycle I and Cycle II, this Classroom Action Research is a Quantitative Research. The results found in this study were that the majority of students with a lack of interest in learning history in Class X Motorcycle Engineering, many students thought that learning history was boring due to the use of learning methods that were less interesting, less interactive, and did not involve students directly in use of learning methods. That's why an innovation is needed in the form of a history learning method. The Small Group Discussion Method is recommended for history teachers as a method that can be a solution to the problems raised so that learning history is expected to be more enjoyable learning and the goals of learning history can be fulfilled.